On the Way to "Conscious" Capitalism: From Marx to Modernity - Tkachenko, Irina Nikolaevna (Economy of Regions, 2018)
The article provides a scientific overview of the evolution of views on the capitalist development from Marx to our days through the prism of the need of social transformations, changes in the value, moral and ethical foundations of the modern capitalism. I consider the basic models of transition to the so-called «conscious» capitalism: stakeholder model, model of corporate social responsibility, model of democratization of property relations (the model of shared capitalism), and directly the model of «conscious» capitalism. The article highlights the relevance of transition from the primacy of proprietary thinking, the desire of owners to maximize shareholder value and increase their welfare to the stakeholder model, which takes into account the interests of a wide range of stakeholders. The trust can be appropriately considered as a condition for implementing the stakeholder model, which provides an opportunity for the development of civilized, socially-oriented relations in business and the economy as a whole. The model of corporate social responsibility contributes to the implementation of common values and its significance for a new stage in the evolution of capitalism. I compare the approaches to the democratization of property relations and shared capitalism on the example of foreign and Russian experience. I conclude that the introduction of the principles of conscious capitalism is not yet a generally accepted practice, which is explained in many ways by different levels of capitalist development. At the same time, the importance of influencing the business model of «conscious» capitalism forces modern capitalists to rethink market opportunities, to transform traditional capitalist values to the concept of common values and to use additional benefits to increase the sustainability of society.